Nivolumab plus chemotherapy in first-line metastatic non-small-cell lung cancer: results of the phase III CheckMate 227 Part 2 trial - Borghaei, H; O'Byrne, K J; Paz-Ares, L; Ciuleanu, T-E; Yu, X; Pluzanski, A; Nagrial, A; Havel, Libor; Kowalyszyn, R D; Valette, C A; Brahmer, J R; Reck, M; et al. (ESMO open, 2023)
BACKGROUND: In CheckMate 227 Part 1, first-line nivolumab plus ipilimumab prolonged overall survival (OS) in patients with metastatic non-small-cell lung cancer (NSCLC) and tumor programmed death-ligand 1 (PD-L1) expression ≥1% versus chemotherapy. We report results from CheckMate 227 Part 2, which evaluated nivolumab plus chemotherapy versus chemotherapy in patients with metastatic NSCLC regardless of tumor PD-L1 expression. PATIENTS AND METHODS: Seven hundred and fifty-five patients with systemic therapy-naive, stage IV/recurrent NSCLC without EGFR mutations or ALK alterations were randomized 1 : 1 to nivolumab 360 mg every 3 weeks plus chemotherapy or chemotherapy. Primary endpoint was OS with nivolumab plus chemotherapy versus chemotherapy in patients with nonsquamous NSCLC. OS in all randomized patients was a hierarchically tested secondary endpoint. RESULTS: At 19.5 months' minimum follow-up, no significant improvement in OS was seen with nivolumab plus chemotherapy versus chemotherapy in patients with nonsquamous NSCLC [median OS 18.8 versus 15.6 months, hazard ratio (HR) 0.86, 95.62% confidence interval (CI) 0.69-1.08, P = 0.1859]. Descriptive analyses showed OS improvement with nivolumab plus chemotherapy versus chemotherapy in all randomized patients (median OS 18.3 versus 14.7 months, HR 0.81, 95.62% CI 0.67-0.97) and in an exploratory analysis in squamous NSCLC (median OS 18.3 versus 12.0 months, HR 0.69, 95% CI 0.50-0.97). A trend toward improved OS was seen with nivolumab plus chemotherapy versus chemotherapy, regardless of the tumor mutation status of STK11 or TP53, regardless of tumor mutational burden, and in patients with intermediate/poor Lung Immune Prognostic Index scores. Safety with nivolumab plus chemotherapy was consistent with previous reports of first-line settings. CONCLUSIONS: CheckMate 227 Part 2 did not meet the primary endpoint of OS with nivolumab plus chemotherapy versus chemotherapy in patients with metastatic nonsquamous NSCLC. Descriptive analyses showed prolonged OS with nivolumab plus chemotherapy in all-randomized and squamous NSCLC populations, suggesting that this combination may benefit patients with untreated metastatic NSCLC.
Keywords: nádory plic; Neoplasm Recurrence, Local; Lung Neoplasms; B7-H1 Antigen; Carcinoma, Squamous Cell; antigeny CD274; lidé; nivolumab; spinocelulární karcinom; Carcinoma, Non-Small-Cell Lung; nemalobuněčný karcinom plic; Nivolumab; lokální recidiva nádoru; Humans